(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A high-speed motor is a workable way to achieve motor reduction in an electric vehicle (EV). A switching reluctance motor (SRM) can be utilized for high-velocity drives because of its robust and straightforward rotor construction. The driving concept is somewhat noisy and vibrational, but it works well. Because conventional techniques of current excitation entail a great deal of complexity, torque controllers are infamously hard to construct. It has been proposed that the fuzzy with vector control could help SRM drive overcome these problems. Vector control has not yet been applied to the SRM in the high-speed drive. The best driving parameters, such as bus voltage and switching frequency, are explained in this article using fuzzy control to run the SRM in the high-speed range. It has been demonstrated that fuzzy with vector control can operate the suggested SRM in the high-speed region, resulting in the least amount of vibration. Among the terms used in the index are vector control, fuzzy logic, and high-speed drive.